Ductile Damage and Fatigue Behavior of Semi-Finished Tailored Blanks for Sheet-Bulk Metal Forming Processes - Besserer, Hans-Bernward; Hildenbrand, Philipp; Gerstein, Gregory; Rodman, Dmytro; Nuernberger, Florian; Merklein, Marion; Maier, Hans Juergen (Journal of Materials Engineering and Performance, 2016)
To produce parts from sheet metal with thickened functional elements, bulk forming operations can be employed. For this new process class, the term sheet-bulk metal forming has been established recently. Since sheet-bulk metal forming processes such as orbital forming generates triaxial stress and strain states, ductile damage is induced in the form of voids in the microstructure. Typical parts will experience cyclic loads during service, and thus, the influence of ductile damage on the fatigue life of parts manufactured by orbital forming is of interest. Both the formation and growth of voids were characterized following this forming process and then compared to the as-received condition of the ferritic deep drawing steel DC04 chosen for this study. Subsequent to the forming operation, the specimens were fatigued and the evolution of ductile damage and the rearrangement of the dislocation networks occurring during cyclic loading were determined. It was shown, that despite an increased ductile damage due to the forming process, the induced strain hardening has a positive effect on the fatigue life of the material. However, by analyzing the fatigued specimens a development of the ductile damage by an increasing number of voids and a change in the void shape were detected.
LFT Import::2019-07-29 (2149)
Keywords: DC04; ductile damage; orbital forming; sheet-bulk metal forming